Severe toxoplasmosis imported from tropical Africa in immunocompetent patients: A case series. Issue 35 (May 2020) - Leroy, Jordan; Houzé, Sandrine; Dardé, Marie-Laure; Yéra, Hélène; Rossi, Benjamin; Delhaes, Laurence; Gabriel, Frédéric; Loubet, Paul; Deleplancque, Anne-Sophie; Senneville, Eric; Ajana, Faïza; Sendid, Boualem; et al.
Abstract: Background: Toxoplasmosis is a zoonosis caused by the protozoan Toxoplasma gondii . In immunocompetent patients the infection is usually benign. However, cases of severe and even lethal primo-infections are regularly reported in South America. In contrast, data from tropical Africa are fragmentary. Methods: Data for French cases of severe toxoplasmosis acquired between 2013 and 2018, in tropical Africa and among immunocompetent patients were collected retrospectively in 2018. Results: Four male patients with a mean age of 34-years were identified. All infections originated in West or Central Africa. The clinical presentations were heterogeneous: two patients had severe disseminated toxoplasmosis, of which one presented with chorioretinitis associated with myositis and the other with febrile pneumopathy; one patient presented with post-infectious acute cerebellar ataxia and the final case had general symptoms and skin manifestations. The diagnosis of acute toxoplasmosis was confirmed by serology in four patients. Molecular diagnosis confirmed T. gondii infection in three patients with Africa 1 as the dominant genotype. The infection was cured with anti-infective treatment in all four patients. Ocular sequelae were reported in the two patients with chorioretinitis. Conclusions: Imported cases of severe toxoplasmosis in immunocompetent patients are rare in France. However, this aetiology should be evoked rapidly in a patient with a severe infectious syndrome who has recently visited or originated from tropical Africa.